The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.21608/jppp.2017.46964
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Quality and Natural Infestation with Insect and Disease of Four Sugarcane Varieties as Affected by Different Levels of Potassium Fertilization

Abstract: The present experiments were carried out in El-Mattana Research Station (latitude of 25.25°N and longitude of 32.31°E), Agricultural Research Center, Luxor Governorate, Egypt. The present work was conducted on two plant cane crops grown in 2015/2016 and 2016/2017 seasons to study the yield, quality and natural of infestation with lesser sugarcane borer, Chilo agamemnon Bles., and pokkah boeng disease (Fusarium moniliforme Sheldon) and other diseases of four sugarcane varieties (G.T.54-9, G.2003-47, Ph 8013 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 1 publication
(5 reference statements)
7
7
0
Order By: Relevance
“…However, the difference in purity% between ʻG.2004-27ʼ promising variety and each the commercial variety ʻG.T.54-9ʼ and ʻG.84-47ʼ promising variety were insignificant, in the plant and 1st ratoon cane. These results are in line with those obtained by El-Geddawy, et al and Fahmy,et al [4,10].…”
Section: Purity Percentagesupporting
confidence: 93%
See 2 more Smart Citations
“…However, the difference in purity% between ʻG.2004-27ʼ promising variety and each the commercial variety ʻG.T.54-9ʼ and ʻG.84-47ʼ promising variety were insignificant, in the plant and 1st ratoon cane. These results are in line with those obtained by El-Geddawy, et al and Fahmy,et al [4,10].…”
Section: Purity Percentagesupporting
confidence: 93%
“…However, the difference in this trait between G.84-47 and ʻG.2003-47ʼ was insignificant, in the plant cane. Varietal differences in cane yield were observed by El-Sogheir and Abd el Fattah and Fahmy, et al [3,10].…”
Section: Cane Yield/hamentioning
confidence: 98%
See 1 more Smart Citation
“…However, the difference in this trait between G.84-47 and G.2003-47 was insignificant, in the plant cane. Varietal differences in cane yield were observed by El-Sogheir & Abd El-Fattah (2009) and Fahmy, et al (2017). Cane yield was significantly influenced by the interaction between inter-row spacing and tested cane varieties in the plant cane and 1 st ratoon.…”
Section: Cane Yield/ton Per Hamentioning
confidence: 89%
“…However, the variance between the two promising genotypes namely G.2003-47 and G.2003-49 in the studied traits was mostly insignificant. Fahmy et al (2017) showed that the sugarcane varieties differed significantly in their susceptibility to C. agamemnon infestation. The highest bored stalks% was observed in G.2003-47 and G.T.54-9 varieties during the first and second season respectively.…”
mentioning
confidence: 99%